2011
DOI: 10.1021/jo2014214
|View full text |Cite
|
Sign up to set email alerts
|

Chameleonic Reactivity of Vicinal Diazonium Salt of Acetylenyl-9,10-anthraquinones: Synthetic Application toward Two Heterocyclic Targets

Abstract: The nature of products in the diazotization of 1-amino-2-acetylenyl-9,10-anthraquinones strongly depends on the nature of substituents at both the alkyne and at the anthraquinone core. Donor substitution (NHAr, OH) at the fourth position stabilizes the diazonium salt at C1, decelerating electrophilic cyclization at the arylethynyl substituent at C2. This effect allows the replacement of the diazonium with azide group and subsequent closure into isoxazole ring with preservation of the alkyne. In contrast, elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 55 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…The necessity of the nucleophile for cyclization was first noted by Overman and Sharp, who found that the 6‐(π‐vinylendo)‐endo‐dig closure occurred only in the presence of the iodide nucleophile . Similarly, alkynyl Richter cyclizations onto aryl diazonium salts are assisted by external species . Interestingly, the regioselectivity for these latter closures can be controlled either with temperature or the nature of the preexisting cyclic core (Scheme ) …”
Section: Extension 4: Promoted Cyclizationsmentioning
confidence: 98%
“…The necessity of the nucleophile for cyclization was first noted by Overman and Sharp, who found that the 6‐(π‐vinylendo)‐endo‐dig closure occurred only in the presence of the iodide nucleophile . Similarly, alkynyl Richter cyclizations onto aryl diazonium salts are assisted by external species . Interestingly, the regioselectivity for these latter closures can be controlled either with temperature or the nature of the preexisting cyclic core (Scheme ) …”
Section: Extension 4: Promoted Cyclizationsmentioning
confidence: 98%
“…The factors responsible for the competition between the two cyclization directions were analyzed in detail by using vic ‐acetylenylamino‐9,10‐anthraquinones as the model substrates 35. The high penalty for including a linear sp‐hybridized vinyl cation in a cycle disfavors the “ endo ” closure in the direct cycloaromatization mechanism 36,37.…”
Section: Ionic Cycloaromatization In Ionic Substrates Is An Old Comentioning
confidence: 99%
“…This, in turn, streamlined the synthesis of several analogues. Here, the reactive capacity of the diazo-salts of vic-acetylenyl-9,10-anthraquinones [20] was used to demonstrate that the structure of the transformation products during diazotization of 1amino-2-acetylenyl-9,10-anthraquinones was strongly dependent on the nature of the substituents in the alkynes and the anthraquinone nucleus ( Figure 16).…”
Section: Chemical Propertiesmentioning
confidence: 99%